Knockdown of ghAlba_4 and ghAlba_5 Proteins in Cotton Inhibits Root Growth and Increases Sensitivity to Drought and Salt Stresses - Magwanga, Richard Odongo; Kirungu, Joy Nyangasi; Lu, Pu; Cai, Xiaoyan; Xu, Yanchao; Wang, Xingxing; Zhou, Zhongli; Hou, Yuqing; Agong, Stephen Gaya; Wang, Kunbo; Liu, Fang (Frontiers in Plant Science, 2019)
We found 33, 17 and 20 Alba genes in Gossypium hirsutum, G. arboreum and G. raimondii, respectively. The Alba protein lengths ranged from 62 to 312 aa, the molecular weight (MW) from 7.003 to 34.55 kDa, grand average hydropathy values of -1.012 to 0.609 and isoelectric (pI) values of -3 to 11. Moreover, miRNAs such as gra-miR8770 targeted four genes, gra-miR8752 and gra-miR8666 targeted three genes, each and gra-miR8657 a, b, c, d, e targeted 10 genes each, while the rests targeted 1 to 2 genes each. Similarly, various cis-regulatory elements were detected with significant roles in enhancing abiotic stress tolerance, such as CBFHV (RYCGAC) with a role in cold stress acclimation among others. Two genes, Gh_D01G0884 and Gh_D01G0922 were found to be highly induced under water deficit and salt stress conditions. Through virus-induced gene silencing (VIGS), the VIGS cotton plants were found to be highly susceptible to both water deficit and salt stresses, the VIGS plants exhibited a significant reduction in root growth, low cell membrane stability (CMS), saturated leaf weight (SLW), chlorophyll content levels and higher excised leaf water loss (ELWL). Furthermore, the stress-responsive genes and ROS scavenging enzymes were significantly reduced in the VIGS plants compared to either the wild type (WT) and or the positively controlled plants. The VIGS plants registered higher concentration levels of hydrogen peroxide and malondialdehyde, with significantly lower levels of the various antioxidants evaluated an indication that the VIGS plants were highly affected by salt and drought stresses. This result provides a key foundation for future exploration of the Alba proteins in relation to abiotic stress.